Extracellular matrix remodeling in the tumor immunity - Du, Wei; Xia, Xueming; Hu, Fan; Yu, Jiayun (Frontiers in Immunology, 2024)
The extracellular matrix (ECM) is a significant constituent of tumors, fulfilling various essential functions such as providing mechanical support, influencing the microenvironment, and serving as a reservoir for signaling molecules. The abundance and degree of cross-linking of ECM components are critical determinants of tissue stiffness. In the process of tumorigenesis, the interaction between ECM and immune cells within the tumor microenvironment (TME) frequently leads to ECM stiffness, thereby disrupting normal mechanotransduction and promoting malignant progression. Therefore, acquiring a thorough comprehension of the dysregulation of ECM within the TME would significantly aid in the identification of potential therapeutic targets for cancer treatment. In this regard, we have compiled a comprehensive summary encompassing the following aspects: (1) the principal components of ECM and their roles in malignant conditions; (2) the intricate interaction between ECM and immune cells within the TME; and (3) the pivotal regulators governing the onco-immune response in ECM.